The therapeutic and psychosocial interaction in enhancing drug targets - Musa, Ramli; Sulaiman, Ahmad Hatim (Bentham Science, 2018)
The holistic standpoint of biopsychosocial importance of mediation is crucial in the perception regarding on how the psychopharmacological agent acts. This understanding is indeed important when dealing with patient's expectation and hope, specifically during their illness and recovery process. In clinical setting, the fundamental knowledge on know-how art of prescribing medication and dietary advice can be of great help in the real-world practice of medicine. Subsequently, this manoeuvre may influence the choice of the pharmacological agents, dietary choice of intake and managing the adverse-effect of the existing drug intervention routine. The relationship between the mind-body is well described in the literature especially in the context of pharmacological therapy. The relationship is important in order to be understood for the management of patients in the clinical settings. Research studies have been done to ascertain the role of the psychosocial contributing factors, and how they may influence an individual’s experience of drug targets. In this thematic issue, the articles focussed on the role of drug targets, which was augmented by the emotional-cognitive and behavioral mediation in enhancing the effects of biological therapy. Emotionalcognitive determinants may influence the processing of neurochemical actions, e.g. the dopamine-oxytocin-nitric oxide neural pathway in patients who were given treatment in order to improve their sexual intimacy with his or her partner. These determinants are also relevant while elaborating the role of psychopharmacological agents in alleviating the patient’s somatic symptoms. Behavioural modification advice may help patients regain their self-confidence in their journey to recovery, despite petite guidance given by the clinician. The purpose of biopsychopsychological input, i.e. intimacy-relationship, cognition and emotional states are important in helping the patient’s self-esteem with successful treatment of the PDE-5 inhibitors. Selecting the right psychopharmacological agents to reduce the sexual-adverse effect of drugs is essential in patients with both depression and schizophrenia. The roles of new novel antidepressants are portrayed in its multi-modality function of treating depression. Antidepressant’s effect in managing physical symptoms is important. The stress model diathesis of alcohol in mental health was underlined in the perspective of neuronal basis of cognition memory. In the present thematic issue, the association of serotonin selective reuptake inhibitors and female sexual dysfunction was discussed with special emphasis on its treatment. Interesting articles on the antinociceptive effect of Mitragyna speciosa, the phosphodiasterase 5-inhibitors (PDE-5i) for erectile dysfunction, the recent approaches on treatment of alcohol addiction, the neurobiology of hypersexuality and its treatment, role of atypical antipsychotics in sexuality, treatment of anxiety disorders with Vortioxetine and the role of dietary compounds in the treatment for anxiety disorders were highlighted. Last but not the least, the present issue also focussed on the use of antidepressants for physical and psychological symptoms in cancer and discussed the dietary issue in the biopsychopsychological context of treatment, which included tocopherol and tocotrienol.